Assessment of the functional state of the body and the risk of developing carditis in patients with Lyme disease - S.O. Nykytyuk (Zaslavsky O.Yu., 2022)
Lyme disease is the most common disease transmitted by Ixodes ticks. We present a case of Lyme carditis in a 13-year-old boy. Clinical and immunological research methods (enzyme-linked immunosorbent assay, blot) were used. The child's condition is of medium severity due to skin and intoxication syndromes and carditis. During the examination, a child was diagnosed with Lyme carditis. A feature of the presented case is the appearance of carditis associated with a tick bite in a child. We believe that educating healthcare professionals about Lyme disease should help practitioners differentiate it from other conditions and improve treatment outcomes.